Hak Asasi Manusia Dalam Islam - Hafniati, Hafniati (AL-ADYAN, 2018)
Human rights are fundamental rights that are inherent in human beings and cannot be eliminated by humans, not by someone, organization or anything but purely a gift from Allah SWT. Muslims must be aware of and understand the rights they have as stated in the Koran. Al-Qur'an as the first source of law for Muslims has laid the basic foundation of human rights and truth and justice, long before any thoughts about it arose in the world community. This can be seen in the provisions contained in the Qur'an, among others: the Right to Life, the Right to Freedom, the right to gain knowledge / education, the right to self respect and the right to possess. In the context of Indonesian-ness, Human Rights found its relevance if it was built based on the orientation of the maqasid as-syari'ah (the basic objectives of sharia), namely to realize and maintain the goodness and prosperity of society. the interests of society, this became known as mashlahah ‘ammah.